PSYCHOLOGY AND STRUCTURE OF AN ATHLETE PERSONALITY (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article discusses the psychology of the athlete's personality. Revealed main approaches to its study. The features of activity in sports, the structure of the athlete's personality, psychological professional qualities are considered.